Spiritual avalanche - Hill, Stephen, 1954- (Lake Mary, Florida : Charisma House, 2013)
"This is a wake up call and vivid warning to readers through a vision of an avalanche that God gave Steve Hill, which represents the false and heretical teachings from pastors and teachers that are spreading to Christians worldwide. Hill shares how every aspect of his vision relates to Christians today. The snow represents the false teaching that is steadily falling on the ears of many Christ followers, covering with many layers the solid foundational truth of Christ. Heresies including universalism, the deification of man, overemphasized grace, and many more that will ultimately destroy the spiritual lives of many. What happens when snow keeps falling, creating the dangerous threat of an avalanche? Those who heed the warnings are saved, but those who fail to listen are caught in a deadly trap. Readers will be challenged to understand these dangers and what they can do to help tear down these false teachings in order to secure a layer of solid, biblical instruction that will establish truth in the work of the Gospel, and help us avoid spiritual destruction."--Amazon website.
Includes bibliographical references.
Keywords: Christian heresies; Theology, Doctrinal